Clinical Outcomes of Transplanted Modified Bone Marrow–Derived Mesenchymal Stem Cells in Stroke: A Phase 1/2a Study. Issue 7 (July 2016) - Steinberg, Gary K.; Kondziolka, Douglas; Wechsler, Lawrence R.; Lunsford, L. Dade; Coburn, Maria L.; Billigen, Julia B.; Kim, Anthony S.; Johnson, Jeremiah N.; Bates, Damien; King, Bill; Case, Casey; McGrogan, Michael; et al.
Abstract : Background and Purpose—: Preclinical data suggest that cell-based therapies have the potential to improve stroke outcomes. Methods—: Eighteen patients with stable, chronic stroke were enrolled in a 2-year, open-label, single-arm study to evaluate the safety and clinical outcomes of surgical transplantation of modified bone marrow–derived mesenchymal stem cells (SB623). Results—: All patients in the safety population (N=18) experienced at least 1 treatment-emergent adverse event. Six patients experienced 6 serious treatment-emergent adverse events; 2 were probably or definitely related to surgical procedure; none were related to cell treatment. All serious treatment-emergent adverse events resolved without sequelae. There were no dose-limiting toxicities or deaths. Sixteen patients completed 12 months of follow-up at the time of this analysis. Significant improvement from baseline (mean) was reported for: (1) European Stroke Scale: mean increase 6.88 (95% confidence interval, 3.5–10.3; P <0.001), (2) National Institutes of Health Stroke Scale: mean decrease 2.00 (95% confidence interval, −2.7 to −1.3; P <0.001), (3) Fugl-Meyer total score: mean increase 19.20 (95% confidence interval, 11.4–27.0; P <0.001), and (4) Fugl-Meyer motor function total score: mean increase 11.40 (95% confidence interval, 4.6–18.2; P <0.001). No changes were observed in modified Rankin Scale. The area of magnetic resonance T2 fluid-attenuated inversion recovery signal change in the ipsilateral cortex 1 week after implantation significantly correlated with clinical improvement at 12 months ( P <0.001 for European Stroke Scale). Conclusions—: In this interim report, SB623 cells were safe and associated with improvement in clinical outcome end points at 12 months. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01287936. Abstract : Supplemental Digital Content is available in the text.